Analisis Efektivitas Dan Implikasi Penerapan Amsilati Dalam Pembelajaran Bahasa Arab - Irsyad, Ainun Najich Jaya Al-Irsyad; Wulandari, Nawang (MUHIBBUL ARABIYAH: Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze the application of the Amsilati book in Arabic language learning and evaluate its effectiveness and implications for the learning process. The Amsilati book, known as a pattern-based Arabic grammar learning method, is adopted as a teaching aid to facilitate the understanding of shorof rules among middle-level students. The research approach used is qualitative-descriptive with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the use of Amsilati can significantly improve students' understanding and accuracy in identifying changes in word form (tashrif). In addition, this method also has a positive impact on students' learning motivation because of its systematic and interactive presentation. The implications of the application of the Amsilati book include the need for continuous teacher training and curriculum adjustments so that this method can be optimally integrated into shorof learning at various levels of education. Keywords: Amsilati, Arabic, learning effectiveness, pattern method, educational implications.